Avaliação de câmara de dessorção de metano e sulfeto de hidrogênio dissolvidos em efluentes de reatores USAB tratando esgoto doméstico - Belinazir Costa do Espirito Santo (2017)
The presence of methane gases and hydrogen sulfide dissolved in the liquid effluent of UASB reactors is a problem that has been recurrent the concern of recovery of the gases of potential energy (methane in high concentrations), control of greenhouse gases (fugitive methane in low concentrations) and odorants (hydrogen sulfide.). This work conducte experiments on the evolution of the desorption chamber (CD) technique to control these gases dissolved in the effluent. This chamber was tested in a pilot scale, with the useful height characteristics of 1.0 and 1.5 m, to evaluate: the effects of surface hydraulic load variation (CHS), fall height effects, and packed effects in the removal of methane and hydrogen sulfide. By varying the rQ ratio in the DC of 1.0 m, result in efficiencies of 50% for methane removal and 51% for hydrogen sulfide, under conditions of CHS of 1.0 m³ / m².min and rQ at 8.0. At low affluent (CHS of 0.1 m³ / m².min) the high rQ ratios did not improve system performance. The best results for this operational phase occurred in the rQ 54.7, with 61% removal efficiencies of methane and 68% of hydrogen sulfide. However, the 1.5 m high desorption chamber operated on an intermediate hydraulic load indicated that increasing the drop height improve the removal efficiency of the dissolved methane at mean values of 64% in the rQ 12.5. However, there were no increments for the dissolved sulfide gas. The results also indicated that the best control efficiencies were found in rQ 8.0 and 1.6 respectively. In these cases, the experiments shown high dilution of the residual (1.0% of methane and 300 ppm of hydrogen sulfide). When the DC was packed, such efficiencies reached 89% and 86% respectively for methane and hydrogen sulfide compounds. In these cases, it was possible to evaluate that the desorption mechanism was responsible for the recovery methane gas with 22%, and the oxidation, in turn, was the predominant mechanism for the removal of hydrogen and 3% was precipitated as elemental sulfur.